Niosome Preparation Techniques and Structure—An Illustrated Review - Saeid Mezail Mawazi; Yi Ge; Riyanto Teguh Widodo (Pharmaceutics)
A comprehensive review of recent research on niosomes was conducted using a mixed methodology, including searches in databases such as Scopus, PubMed, and Web of Science (WoS). Articles were selected based on relevance. The current review examines the historical development of niosomes focusing on the methods of preparations and the contemporary strategies and prospective advancements within the realm of drug delivery systems, highlighting innovative approaches across transdermal, oral, and cellular delivery. This review reported the method of niosomes preparations including a new and novel approach for the preparation of niosomes known as the ball milling method (BM). This technique allows for the precise manipulation of size and shape, leading to improvements in drug release, encapsulation efficiency, and uniformity compared to traditional methods. Niosomes can serve as carriers for delivering various types of drugs, including hydrophobic, hydrophilic, and amphiphilic. This improves the efficiency of encapsulating different drugs, the size of targeted particles, and the desired zeta potential. This is achieved by using a specific charge-inducing agent for drug delivery and targeting specific diseases. These efforts are crucial for overcoming the current limitations and unlocking the full therapeutic potential of modern medicine.